Tablespoon Sterilization Devices Use Ultraviolet (UV) Automatically To Prevent The Spread Of A Covid-19 - Rika Apriliana; Didik Riyanto; Rhesma Intan Vidyastari (JEEE-U (Journal of Electrical and Electronic Engineering-UMSIDA), 2022)
A spoon is a tool to be used instead of a hand in reaching for something. It was rounded, hollow, and round. Most of the use of spoons apart from home is also used extensively by food merchants. Tablespoons among the traders were used interchangeably by the buyers. The cleanliness of eating utensils is an important factor and has an impact on the quality of food. Less hygenic washing may include bacteria such as e. coli, vibrio, clostridium, salmonella, staphylococktail, bacillius sp. for that matter, equipment laundering is essential. A study of the problem will prevent the spread of various viruses and bacteria. One is by making an instrument that can be used to sterilize the tablespoon by using a uv exposure. According to tests taken at upt the ponorogo area health lab, feeding utensils are said to be sterile ata minimum of 5 minutes of the uv fishing and broadcasting process.